PENDAMPINGAN PENGEMBANGAN POTENSI KAMPUNG WISATA LANGENASTRAN MENUJU SUSTAINABLE TOURISM DEVELOPMENT - Nugraha, Bima Setya; Mayandini, Haritsa; Putra, Fariza Ardhya; Madani, Hisyam; Maulana, Naufal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
LANGENASTRAN Village is one of the areas in Yogyakarta City. Langenastran is known as a street and at the same time a strategic village in building tourism and culture, lies in the territory within the Kraton Yogyakarta. Strategic location and also a very rich cultural heritage should be able to attract tourists to come. But it was still less tourists who visit. This is caused by the management of tourism in Langenastran not maximal because of the absence of good governance. Therefore, it is necessary to implement a community service in order to help the community in Langenastran in order to have better selling and governance value. The method used is the method of mentoring and simulation methods. Stages implemented in community service include: conducting meetings in the form of internal team meetings and meetings to coordinate the implementation of activities; met some community leaders to discuss Langenastran Village in the future and how to develop Langenastran will include how to make tour packages, attractions and good organizational structure. Keywords: Langenastran, Potential Jemparingan, Community Service